2013
DOI: 10.1186/1472-6963-13-28
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with clinical practice guidelines for breast cancer treatment: a population-based study of quality-of-care indicators in Italy

Abstract: BackgroundIt has been documented that variations exist in breast cancer treatment despite wide dissemination of clinical practice guidelines. The aim of this population-based study was to evaluate the impact of regional guidelines (Piedmont guidelines, PGL) for breast cancer diagnosis and treatment on quality-of-care indicators in the Northwestern Italian region of Piedmont.MethodsWe included two samples of women aged 50–69 years with incident breast cancer treated in Piedmont before and after the introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…Other indicators of quality treatment (such as performing a single operation, not performing axillary dissection or leaving clear margins) remained unchanged with time, possibly because they had already very high percentages of success (between 83 and 96%). The general improvement observed in quality indicators after the introduction of the regional guidelines on breast cancer diagnosis and treatment is in line with the literature (Sacerdote et al, 2013). This effect may be attributed not only to the implementation and diffusion of guidelines in themselves but also to the progressive increase in the coverage of the screening programme protocol, which ensured a strict adherence to recommendations and an optimal pathway of care to women diagnosed through the programme.…”
Section: Appropriateness Indicatorssupporting
confidence: 82%
“…Other indicators of quality treatment (such as performing a single operation, not performing axillary dissection or leaving clear margins) remained unchanged with time, possibly because they had already very high percentages of success (between 83 and 96%). The general improvement observed in quality indicators after the introduction of the regional guidelines on breast cancer diagnosis and treatment is in line with the literature (Sacerdote et al, 2013). This effect may be attributed not only to the implementation and diffusion of guidelines in themselves but also to the progressive increase in the coverage of the screening programme protocol, which ensured a strict adherence to recommendations and an optimal pathway of care to women diagnosed through the programme.…”
Section: Appropriateness Indicatorssupporting
confidence: 82%
“…The collection of data in all hospitals in the Netherlands resulted in 56,927 patients for whom detailed information regarding their work-up and treatment was available for analysis. Several initiatives have shown that improvement of quality of care can be established by measuring quality indicators over time [7][8][9][10][11][12]; however, to the best of our knowledge we are the first to report on a nationwide breast cancer audit with full participation of all hospitals. The use of quality indicators embedded in a national audit providing benchmark information to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of adherence to CPG and the observed trends during the study period corresponded to findings from previous population-based studies from other Western countries (e.g. proportion of patients with BCS receiving radiotherapy: Saarland 2004/05: 85%, region of Piedmont (Italy) 2004: 88%, Canadian regions 2000–2004: ranging between 77% and 83%; chemotherapy in nodal positive patients: Saarland: 73%, region of Piedmont: 64%, Canadian regions: between 53%-68%; antiestrogen treatment in HR positive or mixed patients: Saarland 2000/2001: 79%, Canadian regions: 79%-85%) [ 38 41 ].…”
Section: Discussionmentioning
confidence: 99%